Piloting the Domestic Violence Healthcare Providers’ Survey for Use in Uganda: Testing Factorial Structure and Reliability - Lawoko, Stephen; Mutto, Milton; Guwattude, David (Psychology, 2012)
A number of instruments to assess healthcare workers readiness to screen for Intimate Partner Violence (IPV) in healthcare are now available to researchers. Before application in new settings however, pilot studies assessing their validity are warranted. Aim: In this pilot study, we assessed the factorial structure and reliability of the Domestic Violence Healthcare Provider Survey Scale (DVHPSS) for future use in Uganda. Method: A convenient sample of healthcare workers at a referral hospital in Arua district, Uganda (n = 90) responded to the DVHPSS. Exploratory factor analysis using principle components and Cronbach’s alphas testing for internal reliability were applied on 86 complete individual responses to items of the DVHPSS. Bivariate correlations were run to assess scale distinctiveness. Re- sults: All but one item of the DVHPSS exhibited significant factor loadings. Most subscales emerging from the factor analysis (i.e. Blame victim, professional role resistance and system support sub-scales) were congruent with the original scales. A split of the original victim/provider safety scale was however evident in the current data, forming two distinct scales i.e. victim and provider safety respectively. Items of the original perceived self-efficacy scale exhibited significant factor loadings but under separate factors, indicating that they may not be measuring a uni-dimensional concept in the Ugandan healthcare context. Conclusions: This data confirms the validity and reliability of the DVHSS for use in Uganda. It is how- ever recommended that items be scored in accordance to the specific sub-scales revealed in this study, to improve the structural validity of any assessment using the DVHPSS in Uganda.
Keywords: Domestic Violence Survey; Healthcare; Factorial Structure; Reliability; Uganda